Electro spinning of Polycaprolactone / Hydroxyapatite Composites in Wound Dressing Application - Mohsan, Ali Hasan; Ali, Nadia A. (Iraqi Journal of Physics, 2022)
Polycaprolactone polymer is widely used in medical applications due to its biocompatibility. Electro spinning was used to create poly (ε- caprolactone) (PCL) nanocomposite fiber mats containing hydroxyapatite (HA) at concentrations ranging from 0.05 to 0.4% wt. The chemical properties of the fabricated bio composite fibers were evaluated using FTIR and morphologically using field-emission scanning-electron microscopy (FESEM), Porosity, contact angle, as well as mechanical testing(Young Modulus and Tensile strength) of the nanofibers were also studied. The FTIR results showed that all the bonds appeared for the pure PCL fiber and the PCL/HA nano fibers. The FESEM nano fiber showed that the fiber diameter increased from 54.13 to 155.79 (nm) at the HA values from (0.05 % and 1%wt.). Porosity, wettability of (PCL/HA) composites has improved, and the contact angle has decreased from 103.59o to 85.57o for fibrous scaffolds. The inclusion of hydroxyapatite increased the tensile strength of nano fiber scaffolds, and the maximum tensile strength of 0.4% percent was about 0.127 MPa, with a lowering in elongation to 40%.